Expression of a Cellobiose Phosphorylase from Thermotoga maritima in Caldicellulosiruptor bescii Improves the Phosphorolytic Pathway and Results in a Dramatic Increase in Cellulolytic Activity - Kim, Sun-Ki (Appl Environ Microbiol, 2018)
Members of the genus Caldicellulosiruptor have the ability to deconstruct and grow on lignocellulosic biomass without conventional pretreatment. A genetically tractable species, Caldicellulosiruptor bescii, was recently engineered to produce ethanol directly from switchgrass. C. bescii contains more than 50 glycosyl hydrolases and a suite of extracellular enzymes for biomass deconstruction, most prominently CelA, a multidomain cellulase that uses a novel mechanism to deconstruct plant biomass. Accumulation of cellobiose, a product of CelA during growth on biomass, inhibits cellulase activity. Here, we show that heterologous expression of a cellobiose phosphorylase from Thermotoga maritima improves the phosphorolytic pathway in C. bescii and results in synergistic activity with endogenous enzymes, including CelA, to increase cellulolytic activity and growth on crystalline cellulose. IMPORTANCE CelA is the only known cellulase to function well on highly crystalline cellulose and it uses a mechanism distinct from those of other cellulases, including fungal cellulases. Also unlike fungal cellulases, it functions at high temperature and, in fact, outperforms commercial cellulase cocktails. Factors that inhibit CelA during biomass deconstruction are significantly different than those that impact the performance of fungal cellulases and commercial mixtures. This work contributes to understanding of cellulase inhibition and enzyme function and will suggest a rational approach to engineering optimal activity.